Regional and sustainable development in Malaysia: unravel the tale of rural economic development / Nazmi@Nazni Noordin - Noordin, Nazmi@Nazni (2021)
As a fully developed country to be, Malaysia must ensure that both urban and rural areas develop equally, and poverty level is taking care appropriately. Regional and Sustainable development in Malaysia is design to support the related Sustainable Development Goals (SDGs) such as No Poverty, Zero Hunger, Good Health & Wellbeing, Gender Equality, Decent Work & Economic Growth, Reduced Inequalities, and Sustainable Cities & Communities. At global level, Agenda 21 emerged as one of the world commitments in upholding sustainable development through the 17 Sustainable Development Goals (SDGs) and their 169 targets. All the country around the globe shall achieved their SDGs by the year of 2030 with "no one left behind" in all the activities, especially for the main pillar; economic, social, and environmental through local or regional development plans.